Evaluation of the Aortopathy in the Ascending Aorta: The Novelty of Using Matrix‐Assisted Laser Desorption/Ionization Imaging. Issue 1 (17th December 2020) - Mohamed, Salah A.; Taube, Eliane T.; Thiele, Herbert; Noack, Frank; Nebrich, Grit; Mohamady, Kamal; Hanke, Thorsten; Klein, Oliver
Abstract : Purpose: Histopathological evaluation presents conflicting reports regarding aortic abnormalities. The authors aim to present proof‐of‐concept study to explore the feasibility of matrix‐assisted laser desorption/ionization imaging mass spectrometry (MALDI‐IMS) in combination with histopathology for characterizing alterations in the aneurysmal ascending formalin‐fixed paraffin‐embedded (FFPE) aorta tissue. Experimental design: The authors assess FFPE specimens from patients with a dilated aorta and bicuspid aortic valve (BAV), those with a standard tricuspid aortic valve (TAV), and those with Marfan syndrome (MFS) via histopathology and grade the conditions for elastic fiber fragmentation (EFF) and MALDI‐IMS. The proteins using liquid chromatographic–mass spectrometry are identified and the results are confirmed by immunohistochemistry. Results: There is significant difference in terms of EFF between MFS and BAV, and TAV and BAV. Characteristic peptide signatures and m / z values in the EFF facilitate the characterization among the aortic specimens of BAV, MFS, and TAV. The m / z values from the aortic alpha smooth muscle actin and myosin heavy chains significantly increase in BAV compared with MFS and TAV. These findings are confirmed by immunohistochemistry. Conclusion: The results represent a strategy that uses MALDI‐IMS in combination with histopathology as promising approaches to characterize spatial alteration in the structure of the aneurysmal ascending aorta.